A reputationbased secure scheme in vehicular ad hoc networks. (2015) - Li, Xiaoqing; Liu, Jicheng; Li, Xuejun; Li, Hui
In recent years trust management has become a main method to ensure the security of vehicular adhoc networks (VANETs). However, most of the existing trust establishment approaches cannot handle the rapidly changing environment of VANETs appropriately. In this paper, we propose a Reputationbased Global Trust Establishment scheme (RGTE). The scheme introduces a solution to share the trust information in VANETs safely by applying statistical laws, which makes it more efficient and accurate to establish trust in rapidly changing environment. Moreover, we detect a bad node by dynamic threshold according to realtime reputation status of the network. Analysis shows that RGTE is more effective in confidencebuilding, security assurance and adaptability.